Intracellular targeting of annexin A2 inhibits tumor cell adhesion, migration, and in vivo grafting - Daniela I. Staquicini (Nature Portfolio, 2017)
Abstract Cytoskeletal-associated proteins play an active role in coordinating the adhesion and migration machinery in cancer progression. To identify functional protein networks and potential inhibitors, we screened an internalizing phage (iPhage) display library in tumor cells, and selected LGRFYAASG as a cytosol-targeting peptide. By affinity purification and mass spectrometry, intracellular annexin A2 was identified as the corresponding binding protein. Consistently, annexin A2 and a cell-internalizing, penetratin-fused version of the selected peptide (LGRFYAASG-pen) co-localized and specifically accumulated in the cytoplasm at the cell edges and cell-cell contacts. Functionally, tumor cells incubated with LGRFYAASG-pen showed disruption of filamentous actin, focal adhesions and caveolae-mediated membrane trafficking, resulting in impaired cell adhesion and migration in vitro. These effects were paralleled by a decrease in the phosphorylation of both focal adhesion kinase (Fak) and protein kinase B (Akt). Likewise, tumor cells pretreated with LGRFYAASG-pen exhibited an impaired capacity to colonize the lungs in vivo in several mouse models. Together, our findings demonstrate an unrecognized functional link between intracellular annexin A2 and tumor cell adhesion, migration and in vivo grafting. Moreover, this work uncovers a new peptide motif that binds to and inhibits intracellular annexin A2 as a candidate therapeutic lead for potential translation into clinical applications.